A study on the strategy of successful bumiputra entrepreneurs in the food service in Kedah, Perlis and Penang: concept, food, ambience & business processes / Mohammad Zaki Ayob…[et al.] - Ayob, Mohammad Zaki; Mohd Saman, Fatimah; Yusoff, Mohd Sukor; Abidin, Noorridzwan (Research Management Institute, Universiti Teknologi MARA, Kedah, 2003)
Customer Satisfaction Index (CSI) studies have been the practice of many industries for improving performance through increased customer loyalty. Focusing on factors contributing to customers’ satisfaction is thus an important strategy towards this objective. Food business is an essential part of our lives, and in this fast-moving age, customers’ demand quick and better services from the providers. The research found that those businesses that focus on customer needs and satisfaction tend to be more successful in terms of customer loyalty as compared to their competitors. Perhaps, there is not much option for food service business to focus on other than meeting their customers’ needs. This research utilizes the structural equations modeling to link customer satisfaction to its determinants (predictors of satisfaction) and in turn, to the consequences of satisfaction, which is customer loyalty. The determinants of customer satisfaction (r|2) are perceived quality of “hardware” (^), perceived quality of “software” and perceived value (q,). The research found that all measured variables were closely aligned to both determinants of customer satisfaction. From business strategy perspectives, customers’ recent (previous six months) experiences with restaurants contribute the biggest impact on customer loyalty. The overall attractiveness (ambience) of restaurants is another factor for success in this industry. Other critical success factors include close attention to food freshness, cleanliness, taste, consistency, and all-time restaurant cleanliness. Among the human factors requiring attention are waiters’ responsiveness to customers’ needs. Overall table arrangements are also important to customers. It is hoped that the findings in this research will inspire participating as well as those in the food business to learn and continuously improve on their strategies to attract customers and achieve success.